Cefuroxime-induced anaphylaxis with prominent central nervous system manifestations: A case report - Jianqing Gu; Shuang Liu; Yuxiang Zhi (Journal of International Medical Research, 2019)
Cefuroxime is a second-generation cephalosporin antibiotic that causes immediate hypersensitivity reactions, ranging from mild urticaria to severe anaphylactic shock. Anaphylactic reactions typically involve multiple systems, most notably, the skin and the respiratory and cardiovascular systems. Here, we report the unusual case of a patient who presented with oral cefuroxime-induced anaphylaxis with prominent neurologic manifestations. To identify the drug responsible for the anaphylaxis, we performed skin tests. Based on positive skin-prick test results, the diagnosis of cefuroxime-induced anaphylaxis was confirmed. Therefore, we suggest that clinicians should consider the possibility of a drug-induced anaphylactic reaction when neurologic but not cutaneous symptoms are present. The skin-prick test is a safe and useful diagnostic tool to confirm this kind of immediate drug hypersensitivity.